Visiting Scholars Program to enhance career development among early-career KL2 investigators in Clinical and Translational Science: Implications from a quality improvement assessment. Issue 1 (14th December 2020) - Robb, Sheri L.; Kelly, Thomas H.; King, Victoria L.; Blackard, Jason T.; McGuire, Patricia C.
Abstract: CTSI Career Development Award (KL2) programs provide junior faculty with protected time and multidisciplinary, mentored research training in clinical and translational science research. The KL2 Visiting Scholars Program was developed to promote collaborative cross-CTSA training, leverage academic strengths at host CTSAs, and support the career development of participating scholars through experiential training and the development of new partnerships. This manuscript provides a detailed programmatic description and reports outcomes from post-visit and outcomes surveys. Since 2016, 12 scholars have completed the program, with 6 scheduled to complete it in 2021. Post-visit surveys ( n = 12) indicate all scholars reported the program valuable to career development, 11 reported benefit for research development, and 11 expansion of collaborative networks. Outcomes surveys ( n = 11) revealed subsequent scholar interaction with host institution faculty for 10 scholars, 2 collaborative grant submissions (1 funded), 2 planned grant submissions, 1 published collaborative manuscript, and 3 planned manuscript/abstract submissions. The Visiting Scholars Program is a cost- and time-efficient program that leverages the academic strengths of CTSAs. The program enhanced KL2 scholar training by expanding their professional portfolio, promoting research development, and expanding collaborative networks. Resources to support the program are shared in this report to expedite the development of similar programs at regional and national levels.